The potential use of bio-activated potassium-bearing mineral from East Java for K fertilizer Potensi mineral pembawa kalium asal Jawa Timur yang dibio-aktivasi sebagai pupuk K - Laksmita Prima SANTI; Didiek Hadjar GOENADI (Menara Perkebunan, 2012)
AbstractPotassium (K) is an essential macro-nutrient for crops to support their development, especially in the early stage of growth. Potassium is found in soils and K-bearing minerals but mainly in an unavailable form. The development of an efficient technique in improvement of K solubilization of K-bearing minerals was very strategic to reduce imported conventional K fertilizers, mainly muriate of potash (MOP). The so-called Bio-Kalium (Bio-K) product was constructed by using locally available K-bearing mineral from East Java. The objective of this research was to determine the efficiency and rational dosage of bio-activation K-bearing mineral in comparison with K conventional fertilizer on the growth of cocoa and oil palm seedlings in greenhouse experiment. The strong technical alkaline solution was used to activate K-bearing mineral. The results showed that the application of 4.2 g/cocoa seedling or 6.4 g/oil palm seedling of bio-activated K bearing mineral containing 108 cfu/gram of Burkholderia vietnamiensis Zeo3 strain (Bio-K)  significantly increased of height, leaf number, and stem diameter of the four and six-month-old cocoa and oil palm seedlings respectively.Abstrak Kalium (K) merupakan unsur hara makro esensial yang diperlukan untuk mendukung pertumbuhan tanaman khususnya pada tahap awal perkembangannya. Kalium terdapat di dalam tanah dan mineral pembawa K, tetapi pada umumnya dalam bentuk yang tidak tersedia. Teknik pengembangan untuk meningkatkan kelarutan K dari mineral pembawa K yang efisien sangat strategis untuk mengurangi ketergantungan terhadap pupuk K import, khususnya muriate of potash (MOP). Pupuk Bio-Kalium (Bio-K) dikembangkan dengan menggunakan mineral pembawa K lokal yang terdapat di Jawa Timur. Tujuan penelitian ini untuk menetapkan efisiensi dan dosis rasional dari mineral pembawa K yang di aktivasi dan diperkaya dengan bakteri (bio-aktivasi) dibandingkan dengan pupuk K konvensional terhadap pertumbuhan bibit kakao dan kelapa sawit di rumah kaca. Larutan  basa kuat teknis digunakan untuk meng-aktivasi mineral pembawa K. Hasil yang diperoleh menunjukkan bahwa aplikasi mineral pembawa K yang diaktivasi dan mengandung 108 cfu/g Burkholderia vietnamiensis strain Zeo3 (Bio-K) sebanyak 4,2 g/bibit kakao atau 6,4 g/bibit kelapa sawit dapat meningkatkan masing-masing tinggi, jumlah daun, dan diameter batang bibit kakao umur empat bulan dan kelapa sawit umur enam bulan secara signifikan.